Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2020
DOI: 10.3389/fonc.2020.566637
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Assessment of the WNT/β-Catenin Pathway, CacyBP/SIP, and the Immunoproteasome Subunit LMP7 in Various Histological Types of Renal Cell Carcinoma

Abstract: ObjectiveThe Wnt/ß-catenin pathway plays an important role in pathogenesis of variety cancers. Most studies on changes in WNT/β-catenin pathway in renal cell carcinoma (RCC) apply only to clear cell RCC, while there are no comparative assessments of this signaling pathway in various histological types of renal tumors in the available literature. Additionally, considering the close relationship between WNT/β-catenin signaling, CacyBP/SIP and proteasomal activity, it seemed worth comparing WNT/β-catenin pathway,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
13
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 33 publications
1
13
0
Order By: Relevance
“…Aberrant DNA methylation changes on promoters, enhancers, and gene bodies contribute to alteration of gene expression and consequently affect signaling, regulatory, and metabolic pathways. Renal carcinoma has been associated with MET ( 46 ), Hippo ( 47 ), Wnt ( 48 ), MAPK ( 49 ), NRF2 (nuclear erythroid 2-related factor 2)-ARE (antioxident response element), phosphatidylinositol 3-kinase (PI3K)/AKT/mechanistic target of rapamycin (mTOR) ( 50 ), metabolic, angiogenic, and immune checkpoint–associated pathways ( 51 ). GO and pathway enrichment analysis of the MethylBoostER features mapped to genes show a strong association with genes, processes, and pathways involved in carcinogenesis.…”
Section: Discussionmentioning
confidence: 99%
“…Aberrant DNA methylation changes on promoters, enhancers, and gene bodies contribute to alteration of gene expression and consequently affect signaling, regulatory, and metabolic pathways. Renal carcinoma has been associated with MET ( 46 ), Hippo ( 47 ), Wnt ( 48 ), MAPK ( 49 ), NRF2 (nuclear erythroid 2-related factor 2)-ARE (antioxident response element), phosphatidylinositol 3-kinase (PI3K)/AKT/mechanistic target of rapamycin (mTOR) ( 50 ), metabolic, angiogenic, and immune checkpoint–associated pathways ( 51 ). GO and pathway enrichment analysis of the MethylBoostER features mapped to genes show a strong association with genes, processes, and pathways involved in carcinogenesis.…”
Section: Discussionmentioning
confidence: 99%
“…Numerous studies have shown that various classic signaling pathways, including VHL/HIF1α ( 38 ), PI3K/Akt/mTOR ( 39 ), HGF/met ( 40 ), MAPK ( 41 ) and Wnt/β- Catenin ( 42 ), are implicated in the promotion of ccRCC. ACSL3 expression has been discovered to be positively linked with tumor suppressor genes such as p53, Pten, and VHL.…”
Section: Discussionmentioning
confidence: 99%
“…Many Wnt members were identified as biomarkers for RCC, and some of them were verified as participants in RCC development [ 49 52 ]. Piotrowska et al compared the activation of Wnt/β-catenin pathway among ccRCC, papillary RCC and chromophobe RCC via immunohistochemistry, finding that the Wnt pathway pronouncedly activated in ccRCC [ 53 ]. A classical mechanism of the Wnt pathway is to decrease the amount of phosphorylated GSK3β and cytoplasmic β-catenin as well as upregulate many transcription factors that could upregulate oncogene MYC and CCND1 [ 54 ].…”
Section: Discussionmentioning
confidence: 99%